Pengaruh Pendidikan Kesehatan melalui Media Audio-Visual dalam Meningkatkan Pengetahuan dan Sikap Remaja tentang Bahaya Merokok - Fika Daulian (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2026)
Smoking behavior among adolescents is a major public health concern because it can have negative consequences on both physical and mental health. Low levels of knowledge and attitudes toward the dangers of smoking contribute to the high prevalence of smoking among adolescents. Therefore, health education interventions utilizing audio-visual media are considered effective strategies to enhance understanding in delivering health messages. This study aimed to examine the effect of health education using audio-visual media on improving adolescents' knowledge and attitudes regarding the dangers of smoking. The researchers implemented a quasi-experimental design that included a pretest and a posttest for a single group of participants. The sample consisted of 43 students selected through purposive sampling at SMPN 15 Kendari in 2024. A questionnaire was used as an instrument to measure knowledge and attitudes, while data were analyzed using the non-parametric Wilcoxon Signed Rank Test to identify improvements before and after the intervention. The results showed that health education using audio-visual media about the dangers of smoking significantly increased adolescents' knowledge (Sig. p = 0.000 < α 0.05) and attitudes (Sig. p = 0.012 < α 0.05). In conclusion, health education intervention using audio-visual media significantly impact on improving adolescents' knowledge and attitudes toward the dangers of smoking.